2016
DOI: 10.1039/c6ay01184e
|View full text |Cite
|
Sign up to set email alerts
|

Raman microspectroscopic analysis of fibers in beverages

Abstract: Raman microspectroscopy allows us to distinguish between synthetic and natural fibers in beverage samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 118 publications
(65 citation statements)
references
References 12 publications
0
64
0
1
Order By: Relevance
“…Considering different size classes,t he small fragments (< 50 mm) in particular were underestimated when using an optical microscope,w hereas long fibers (> 200 mm) led to false-positive results (see Figure 3A). [38,39] Another disadvantage of visual identification alone is the lack of information on the exact plastic types of the MP samples.T his allows only limited conclusions on the source and environmental risk of the sample,b ecause different plastic types exhibit different toxicities resulting from the use of additives/plasticizers and coloration. Thei ndispensable need for an additional spectroscopic identification method was also recently shown by Remy et al, [38] who identified 100 %o ft he potential MP fibers deriving from macrofauna in seagrass as cellulose by means of RM.…”
Section: Mp Identification and Quantificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering different size classes,t he small fragments (< 50 mm) in particular were underestimated when using an optical microscope,w hereas long fibers (> 200 mm) led to false-positive results (see Figure 3A). [38,39] Another disadvantage of visual identification alone is the lack of information on the exact plastic types of the MP samples.T his allows only limited conclusions on the source and environmental risk of the sample,b ecause different plastic types exhibit different toxicities resulting from the use of additives/plasticizers and coloration. Thei ndispensable need for an additional spectroscopic identification method was also recently shown by Remy et al, [38] who identified 100 %o ft he potential MP fibers deriving from macrofauna in seagrass as cellulose by means of RM.…”
Section: Mp Identification and Quantificationmentioning
confidence: 99%
“…Thenonstained material is then assigned as microplastic.However,it has already been recognized that only spectroscopic analysis (FTIR or RM) can provide unambiguous proof of the synthetic nature of the non-stained particles/fibers. [38,39] Another disadvantage of visual identification alone is the lack of information on the exact plastic types of the MP samples.T his allows only limited conclusions on the source and environmental risk of the sample,b ecause different plastic types exhibit different toxicities resulting from the use of additives/plasticizers and coloration.…”
Section: Mp Identification and Quantificationmentioning
confidence: 99%
“…During the second-level screening, the full papers were scrutinized, and 112 studies were removed with reasons (S1 Appendix) and seven were included. When the searches were rerun, five more studies were included after the first and second level screening (Fig 1), resulting in 12 studies [60][61][62][63][64][65][66][67][68][69][70][71] finally included in this systematic review.…”
Section: Study Selectionmentioning
confidence: 99%
“…One of these studies cautioned that the staining agent (rose Bengal) may false-negatively exclude some synthetic compounds or false-positively include nonplastic compounds [22]. The second study [23] built on initial methods by applying Raman microspectroscopy (RM) to accurately distinguish between synthetic and cellulose fibres in beer and bottled mineral water (Supplementary Table 1). This investigation indicated the need for further qualitative and quantitative analysis of fibres in beverages [23].…”
Section: Reports Of Microplastics In Drinking Watermentioning
confidence: 99%